2018
DOI: 10.1038/s41419-017-0105-5
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-associated membranes in aging and senescence: structure, function, and dynamics

Abstract: Sites of close contact between mitochondria and the endoplasmic reticulum (ER) are known as mitochondria-associated membranes (MAM) or mitochondria-ER contacts (MERCs), and play an important role in both cell physiology and pathology. A growing body of evidence indicates that changes observed in the molecular composition of MAM and in the number of MERCs predisposes MAM to be considered a dynamic structure. Its involvement in processes such as lipid biosynthesis and trafficking, calcium homeostasis, reactive o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
184
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(184 citation statements)
references
References 145 publications
(182 reference statements)
0
184
0
Order By: Relevance
“…Furthermore, processes requiring ER involvement which directly or indirectly affect mitochondrial shape such as Ca 2+ buffering, mitophagy, and ER‐UPR are all dysregulated with age indicating that ER dysfunction can itself contribute to mitochondrial dynamic dysregulation. Consistent with the importance of ER‐mitochondria encounter structures, ERMES (mitochondria‐ER contact sites, MAM equivalents) are also decreased in senescent yeast cells suggesting that maintenance of ER‐mitochondria proximity might be effective in conservation of organelle function . Whether shared mitochondrial and ER functions and dynamics co‐evolved and whether their interactions can be altered to decrease age‐related organellar dysregulation await further scientific attention.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Furthermore, processes requiring ER involvement which directly or indirectly affect mitochondrial shape such as Ca 2+ buffering, mitophagy, and ER‐UPR are all dysregulated with age indicating that ER dysfunction can itself contribute to mitochondrial dynamic dysregulation. Consistent with the importance of ER‐mitochondria encounter structures, ERMES (mitochondria‐ER contact sites, MAM equivalents) are also decreased in senescent yeast cells suggesting that maintenance of ER‐mitochondria proximity might be effective in conservation of organelle function . Whether shared mitochondrial and ER functions and dynamics co‐evolved and whether their interactions can be altered to decrease age‐related organellar dysregulation await further scientific attention.…”
Section: Introductionmentioning
confidence: 77%
“…Conversely, ER might function to increase DRP1‐independent constriction of the mitochondria if fission rates are low. Indeed, reduced mitochondria‐ER contacts have been reported in aged cells, suggesting that with age ER regulation of mitochondrial dynamics might decline and contribute to age‐associated imbalance in mitochondrial dynamics . Furthermore, in addition to fission proteins, MFN2 but not MFN1 was shown to localize to ER .…”
Section: Introductionmentioning
confidence: 99%
“…Cellular senescence is a form of cell cycle arrest that can develop in response to DNA damage, nutrient deficiency, telomere shortening, oxidative stress, and oncogene activation. Senescence induction is often executed as a barrier against tumorigenesis, but senescent cells can produce growth factors and cytokines, collectively named as the senescent-associated secretory phenotype (SASP), which can promote tumor development 150 . It was demonstrated that co-inhibition of BCL-w and BCL-X L by specific siR-NAs or by a BH3 mimetic (ABT-737) induced apoptosis in senescent human fibroblasts in vitro 151 .…”
Section: Role Of Bcl-w In Cellular Senescencementioning
confidence: 99%
“…Therefore, MAMs are involved in steroid synthesis, phospholipid metabolism, autophagy, inflammation and mitochondrial bioenergetics. Recent studies have described the important role of MAMs in the pathogenesis of several diseases such as senescence, Alzheimer's disease, obesity and myocardial ischemia‐reperfusion . However, the role of MAMs in hypoxia‐induced mitochondrial impairment and injury in ECs remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have described the important role of MAMs in the pathogenesis of several diseases such as senescence, Alzheimer's disease, obesity and myocardial ischemia-reperfusion. [20][21][22][23] However, the role of MAMs in hypoxia-induced mitochondrial impairment and injury in ECs remains unclear.…”
Section: Introductionmentioning
confidence: 99%